Identification and Biochemical Characterization of the Serine Biosynthetic Enzyme 3-Phosphoglycerate Dehydrogenase in Marchantia polymorpha - Akashi, Hiromichi; Okamura, Eiji; Nishihama, Ryuichi; Kohchi, Takayuki; Hirai, Masami Y. (Frontiers in Plant Science, 2018)
L-serine is an important molecule in all living organisms, and thus its biosynthesis is considered to be regulated according to demand. 3-Phosphoglycerate dehydrogenase (PGDH), the first committed enzyme of the phosphorylated pathway of L-serine biosynthesis, is regulated by negative feedback from L-serine in bacteria. In the case of the vascular plant Arabidopsis thaliana, two PGDH isozymes out of three are inhibited by L-serine and activated by L-alanine, L-valine, L-methionine, L-homoserine, and L-homocysteine, suggesting a more complicated regulatory mechanism of L-serine biosynthesis in A. thaliana than in bacteria. However, it remains to be clarified whether the activation mechanism of PGDH by amino acids is conserved in land plants. In this study, we identified the sole isozyme of PGDH in the liverwort Marchantia polymorpha (MpPGDH) and elucidated its biochemical characteristics. MpPGDH cDNA encodes a 65.6 kDa protein that contains a putative transit peptide for chloroplast localization. MpPGDH shares 75–80% identity with A. thaliana isozymes and forms a homotetramer in vitro. Recombinant MpPGDH exhibited an optimal pH of 9.0, apparent Michaelis constants of 0.49 ± 0.04 and 0.096 ± 0.010 mM for 3-PGA and NAD+, respectively, and apparent maximum velocity of 5.65 ± 0.10 μmol⋅min−1⋅mg−1, similar to those of A. thaliana isozymes. Phosphate ions were found to stabilize MpPGDH, suggesting that phosphate ions are also a crucial factor in the regulation of serine biosynthesis via the phosphorylated pathway in Marchantia polymorpha. MpPGDH was inhibited by L-serine in a cooperative manner and was activated by L-alanine, L-valine, L-methionine, L-homoserine, and L-homocysteine to a lesser extent than it is in A. thaliana. The results suggest that an ancestral PGDH of land plants was inhibited byL-serine and slightly activated by five other amino acids.